Enhanced hydrogen storage properties and mechanisms of magnesium hydride modified by transition metal dissolved magnesium oxides. (29th November 2018) - Zhang, J.; Yan, S.; Yu, L.P.; Zhou, X.J.; Zhou, T.; Peng, P.
Abstract: Magnesium hydride (MgH2 ) is a promising on-board hydrogen storage material due to its high capacity, low cost and abundant Mg resources. Nevertheless, the practical application of MgH2 is hindered by its poor dehydrogenation ability and cycling stability. Herein, the influences and mechanisms of thin pristine magnesium oxide (MgO) and transition metals (TM) dissolved Mg(TM)O layers (TM = Ti, V, Nb, Fe, Co, Ni) on hydrogen desorption and reversible cycling properties of MgH2 were investigated using first-principles calculations method. The results demonstrate that either thin pristine MgO or Mg(TM)O layer weakens the MgH bond strength, leading to the decreased structural stability and hydrogen desorption energy of MgH2 . Among them, the Mg(Nb)O layer exhibits the most pronounced destabilization effect on MgH2 . Moreover, the Mg(Nb)O layer presents a long-acting confinement effect on MgH2 due to the stronger interfacial bonding strength of Mg(Nb)O/MgH2 and the lower brittleness of Mg(Nb)O itself. Further analyses of electronic structures indicate that these thin oxide layers coating on MgH2 surface reduce the bonding electron number of MgH2, which essentially accounts for the weakened MgH bond strength and enhanced hydrogen desorption properties of modified MgH2 systems. These findings provide a new avenue for enhancing the hydrogen desorption and reversible cycling properties of MgH2 by designing and adding suitable MgO based oxides with high catalytic activity and low brittleness. Graphical abstract: Highlights: Influences of MgO based oxides on hydrogen storage properties of MgH2 are studied. Thin Mg(Nb)O layer exhibits a pronounced destabilization effect on MgH2 . Thin Mg(Nb)O layer presents a long-acting confinement effect on MgH2 . Modifying mechanisms of MgO based oxides on MgH2 are investigated.